Ebolaviruses: New roles for old proteins - Cantoni, Diego; Rossman, Jeremy S. (PLOS Neglected Tropical Diseases, 2018)
In 2014, the world witnessed the largest Ebolavirus outbreak in recorded history. The subsequent humanitarian effort spurred extensive research, significantly enhancing our understanding of ebolavirus replication and pathogenicity. The main functions of each ebolavirus protein have been studied extensively since the discovery of the virus in 1976; however, the recent expansion of ebolavirus research has led to the discovery of new protein functions. These newly discovered roles are revealing new mechanisms of virus replication and pathogenicity, whilst enhancing our understanding of the broad functions of each ebolavirus viral protein (VP). Many of these new functions appear to be unrelated to the protein’s primary function during virus replication. Such new functions range from bystander T-lymphocyte death caused by VP40-secreted exosomes to new roles for VP24 in viral particle formation. This review highlights the newly discovered roles of ebolavirus proteins in order to provide a more encompassing view of ebolavirus replication and pathogenicity.